CORRELATION OF DIABETES BURNOUT SYNDROME AND QUALITY OF LIFE IN DIABETES MELLITUS: KORELASI SINDROM DIABETES BURNOUT DENGAN KUALITAS HIDUP PADA DIABETES MELLITUS - Nian Afrian Nuari (Akademi Keperawatan Yarsi Samarinda, 2020)
Diabetes mellitus is a disease that is often found in Indonesian society. The number of sufferers increases from year to year. Diabetes Mellitus Sufferers may experience burnout syndrome which is often experienced by other chronic diseases. The purpose of this study was to analyze the relationship between diabetes burnout syndrome and quality of life in Diabetes Mellitus patients. This study used a correlational design. The sample in this study were Diabetes Mellitus patients who met the inclusion criteria, amounting to 55 people. The sampling technique used in this study was purposive sampling. Based on the research indicated that the majority of respondents had diabetes burnout in the moderate category and had the quality of life with an adequate category. The results of data analysis show there was a relationship between diabetes burnout syndrome and the quality of life of DM patients. Diabetes burnout syndrome was a form of saturation experienced by people with DM related to a series of management or treatment that is underway and this is related to the quality of life of patients. Proper education of health workers is needed to reduce the symptoms of diabetes burnout experienced by patients.